2011
DOI: 10.1002/jhet.582
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of new imidazoles from direct reaction of 2,3‐diamino‐1,4‐naphthoquinone with aldehydes

Abstract: in Wiley Online Library (wileyonlinelibrary.com).New imidazoles were easily prepared from 2,3-diamino-1,4-naphthoquinone and stoichiometric quantities of the appropriate aldehydes in dimethyl sulfoxide as a solvent. The reaction proceeded for few hours. The procedure can be generalized to different classes of aldehydes. 2-Methyl-1H-naphtho[2,3-d]imidazole-4,9-dione was also obtained in good yield during refluxing of 2,3-diaminonaphthoquinone in acetic acid. The structure of the newly synthesized imidazoles was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 46 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The reaction mixture was heated to 60 1C for 12 h. Finally the reaction mixture was cooled to RT and then filtered through a filter paper and washed with water to obtain the pure product (1) as a dark blue powder (12 g, yield = 72%). General procedure for synthesis of (2a-2h) 50 A mixture of compound 1 (0.5 g, 2.65 mmol) and the corresponding aldehyde (2.65 mmol) in DMSO (5 mL) was heated at 90 1C with stirring for 6 h. After cooling to room temperature, the precipitate obtained was filtered from the reaction mixture using filter paper and was washed with cold ethanol to obtain the pure product. The products were characterized using 1 H and 13 C NMR and LC-MS techniques.…”
Section: Synthesis and Characterization Of 1 49mentioning
confidence: 99%
“…The reaction mixture was heated to 60 1C for 12 h. Finally the reaction mixture was cooled to RT and then filtered through a filter paper and washed with water to obtain the pure product (1) as a dark blue powder (12 g, yield = 72%). General procedure for synthesis of (2a-2h) 50 A mixture of compound 1 (0.5 g, 2.65 mmol) and the corresponding aldehyde (2.65 mmol) in DMSO (5 mL) was heated at 90 1C with stirring for 6 h. After cooling to room temperature, the precipitate obtained was filtered from the reaction mixture using filter paper and was washed with cold ethanol to obtain the pure product. The products were characterized using 1 H and 13 C NMR and LC-MS techniques.…”
Section: Synthesis and Characterization Of 1 49mentioning
confidence: 99%
“…11,12 Previously, Aly and his group 13 investigated the reaction of 1,8-diaminonaphthalene (as a structure analogous to 2,3-diamino-1,4-naphthoquinone) with π-acceptors. Aly et al 14 have also recently reported that imidazoles derived from 2,3-diamino-1,4-naphthoquinone were easily directly prepared by addition of the appropriate aldehydes in dimethyl sulfoxide as a solvent. The effect of imidazo-isoindole derivatives (mazindol) upon motor and feeding activity, two different avoidance behaviors have been compared with those of δamphetamine in rats.…”
mentioning
confidence: 99%